Joseph Lippman, The Revised Ordinances of Salt Lake City, Utah, Embracing All Ordinances of a General Nature in Force December 20, 1892, Together with the Charter of Salt Lake City, the Amendments Thereto, and Territorial Laws of a General Nature Applicable to Salt Lake City, and the Constitution of the United States, at 284, ch. 26, § 18 (1893) - (:unkn) unknown (General Publisher, 1889)
Any person discharging an air gun, sparrow gun, flipper, or other similar contrivance, within the limits of this city, shall be liable to a fine of not more than twenty-five dollars for every such offense.
--
Keywords: DISCHARGE